UPAYA MENINGKATKAN HASIL BELAJAR MENGENAL NAMA-NAMA ALLAH SWT MELALUI MEDIA QUIZIZZ PADA PEMBELAJARAN DARING - Hildah, I`ing (MIDA : Jurnal Pendidikan Dasar Islam, 2023)
Abstract The purpose of this class action research is to find out the extent of the influence of the use of Quizizz on student learning outcomes on the material of knowing the names of God during a pandemic. The material focuses on 4 Asmaul Husna namely Al-Mumit (Allah Almighty), AlHayyu (Allah Almighty), Al Qayyum (Allah Almighty), and Al-Ahad (Allah Almighty). The subjects of the study were grade 5 students. Data in the study were obtained from observation, documentation and interviews. The data obtained are analyzed by descriptive analysis. The results of the study found that there was an increase in the learning outcomes of grade 5 students on the material after action through the use of Quizizz media. In the first cycle, it is known that there are 50% of students whose results are lacking. Furthermore, in cycle II after the action, the results of 100% of students were not under KKM, with details of 2 students (17%) sufficient criteria, 6 good students (50%) and excellent criteria of 4 students or 33%. Keywords: Learning Outcomes, Names of God, Quizizz Abstrak Tujuan penelitian tindakan kelas ini yaitu untuk mengetahui sejauh mana pengaruh penggunaan Quizizz terhadap hasil belajar siswa pada materi mengenal nama-nama Allah pada masa pandemi. Materi berfokus pada 4 Asmaul Husna yaitu Al-Mumit (Allah Yang Maha Mematikan), Al-Hayyu (Allah Yang Maha Hidup), Al Qayyum (Allah Maha Berdiri Sendiri), dan Al-Ahad (Allah Yang Maha Esa). Subyek penelitian yaitu siswa kelas 5. Data dalam penelitian diperoleh dari observasi, dokumentasi dan wawancara. Data yang diperoleh dianalisis dengan deskriptf. Hasil penelitian diketahui adanya peningkatan hasil belajar siswa kelas 5 pada materi tersebut setelah adanya tindakan melalui pemanfaatan media Quizizz. Pada siklus I diketahui ada 50% siswa yang hasilnya berkriteria kurang. Selanjutnya pada siklus II setelah adanya tindakan diperoleh hasil 100% siswa tidak ada yang di bawah KKM, dengan rincian 2 peserta didik (17%) kriteria cukup, 6 siswa baik (50%) dan kriteria sangat baik sebanyak 4 peserta didik atau 33%. Kata kunci: Hasil Belajar, Nama-Nama Allah, Quizizz